2018
DOI: 10.1111/bjh.15450
|View full text |Cite
|
Sign up to set email alerts
|

The use of erythropoiesis‐stimulating agents is safe and effective in the management of anaemia in myelofibrosis patients treated with ruxolitinib

Abstract: Erythropoiesis-stimulating agents (ESAs) were combined with ruxolitinib in 59 anaemic myelofibrosis patients (93% with Dynamic International Prognostic Scoring System [DIPSS] intermediate-2/high risk; 52·5% transfusion-dependent). Anaemia response (AR) rate was 54% and 76% of patients responded at 5 years. A further 15% displayed minor improvement in anaemia and 78% of patients reduced spleen size. Endogenous erythropoietin levels <125 u/l correlated with a higher AR rate (63% vs. 20%, P = 0·008). No thromboti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 13 publications
3
21
0
Order By: Relevance
“…Consistent with the mechanism of action of JAK2 inhibitors, the main adverse effect of ruxolitinib is anemia, which is observed in ~40% of patients, and thrombocytopenia [136]. The use of erythropoiesis-stimulating agents (ESAs) in combination with ruxolitinib to alleviate anemia was initially discouraged in phase 3 COMFORT I study but some responses were seen in a post hoc analysis from COMFORT II patients [137].…”
Section: Combination Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…Consistent with the mechanism of action of JAK2 inhibitors, the main adverse effect of ruxolitinib is anemia, which is observed in ~40% of patients, and thrombocytopenia [136]. The use of erythropoiesis-stimulating agents (ESAs) in combination with ruxolitinib to alleviate anemia was initially discouraged in phase 3 COMFORT I study but some responses were seen in a post hoc analysis from COMFORT II patients [137].…”
Section: Combination Therapymentioning
confidence: 99%
“…The use of erythropoiesis-stimulating agents (ESAs) in combination with ruxolitinib to alleviate anemia was initially discouraged in phase 3 COMFORT I study but some responses were seen in a post hoc analysis from COMFORT II patients [137]. In a recent multicenter study, ESAs in combination with ruxolitinib led to improvements in anemia in MF patients, with no associated toxicities and with a trend towards better survival [136]. Ruxolitinib has also been tested in combination with danazol, which has been used for the treatment of anemia in MF patients.…”
Section: Combination Therapymentioning
confidence: 99%
“…In a post-hoc analysis, McMullin et al reviewed the use of ESAs in patients receiving ruxolitinib in the COMFORT-II trial and demonstrated the combination was well tolerated, though rarely associated with a substantial benefit [ 51 ]. A subsequent retrospective analysis suggested a more favorable impact of adding ESA to ruxolitinib, with anemia responses occurring in 54% of patients, though the relative timing of ESA initiation to ruxolitinib varied [ 52 ]. While the concept of augmenting red blood cell production via stimulation of erythropoietin (EPO) receptors that are being blocked by downstream JAK2 inhibition seems illogical, ruxolitinib does not result in continuous JAK2 inhibition.…”
Section: Killing Two Birds With Two Stones: Efforts To Manage Anemmentioning
confidence: 99%
“…Crisà et al [34] retrospectively evaluated fifty-nine patients who received ruxolitinib combined with ESAs for anemia and had found that the rate of anemia may be related to the combination of ruxolitinib and ESAs, and lower erythropoietin (EPO) (< 125u/I) level was an obvious predictor of anemia response. Especially, there was no significant negative impact of the ESAs on response to ruxolitinib.…”
Section: Ruxolitinib Combined With Hydroxyurea Is Feasible In Real-womentioning
confidence: 99%